Poetic Breath - Honein, Natalie; Gulla, Amanda; Henze, Adam; Morris, Nicole; Podolski, Adam Garry; Sherman, Molly (Journal of the Canadian Association for Curriculum Studies, 2022)
This special issue of JCACS amplifies and intersects multiple themes that challenge our capacity to access air. We invited research presented at the 2019 International Symposium on Poetic Inquiry, as well as new poetic inquiry that engages, plays with, ignites and challenges notions of action in a time of legislated inaction, work that counteracts silencing the breath inside our bones. We looked for oxygen where there was none. The editors of this special issue all use poetry as a form of inquiry in their lives and academic work, and we are delighted to share the work of our colleagues from the poetic inquiry community. We believe that this issue demonstrates the value of using poetic inquiry in academia to highlight the voices of those underrepresented and thus is a vital contribution to the research community.